ANALISIS RANTAI NILAI UBI KAYU (Manihot esculeta crantz) DI KABUPATEN PATI - Donny Puja Puspito; Kusnandar Kusnandar; Nuning Setyowati (Caraka Tani: Journal of Sustainable Agriculture, 2016)
This study aimed to analyze the value chain mapping, governance, improvement of value chain and marketing margins cassava in Pati regency. The basic method used  descriptive analytical research. The method of determining the location of the research method and the purposive sampling method is done by snowball sampling with 18 respondents. The results showed there are three models of the value chain by five actors, namely farmers, penebas, grinders, realtor, and collectors flour. Value-added activities conducted on cassava farmers, grinders and collectors. While penebas and brokers act as a liaison between value chain actors. Governance cassava value chain is analyzed through three approaches namely coordination structures, rules and regulations, and provider of information and services. The increase in the value chain are identified in several aspects of increase of processes, products, and functions. Enhanced functions effectively needs to be done because it will produce a positive impact on the actors of the value chain. Grinder has a marketing margin of RP 3300 / kg, meaning that most large margin than other players because it has many activities ranging from wet to cassava starch that have added value. While the perpetrators of broker only has a margin of RP 20 / kg for his activities only as an intermediary without any added value from the starch itself.